Low temperature matrix synthesis by activated nitridation of a TiSi2 powder. Issue 13 (October 2017) - Maillé, L.; Le Petitcorps, Y.; Roger, J.
Abstract: This paper describes a new method to prepare a matrix for Ceramic Matrix Composites (CMC) at low temperatures from a solid/gas chemical reaction. Contrary to previous works, a TiSi2 powder is fully nitrided at 1100 °C leading to the formation of Si3 N4 and TiN phases while avoiding the presence of free silicon. This new result can be obtained by the addition of a chemical element promoting a full chemical conversion. In the present case, thermochemical computations led to select nickel (Ni) as this chemical element.